Depth and Nature of Giant Petroleum Discoveries Through Time as an Indicator of Resource Depletion. (8th October 2012) - Railsback, L. Bruce
Summary A striking increase of the depth of giant petroleum discoveries in the past 15 years coincides with a shift to discoveries in subsalt plays that require more challenging exploration and drilling. Technological advances have facilitated these changes, but technological advances alone could not have induced these changes in petroleum exploration on a planet in which shallow and less challenging targets remained in abundance like that of previous decades. Instead, the trends toward greater discovery depths and more challenging plays suggest that most of the conventional petroleum accumulations of the kind that fueled the global economic system of the 1900s have already been found.